ETHNO-BOTANICAL STUDY OF MEDICINAL PLANTS OF PADDAR VALLEY OF JAMMU AND KASHMIR, INDIA - Gupta, Sushil Kumar; P., Sharma O.; S., Raina N.; S., Sehgal (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The Paddar Valley, historically known as Sapphire Valley situated in Kishtwar district, is a prime landmark in the Jammu region of J&K state and is known for its rich cultural and plant diversity because of diverse habitats such as rivers, streams, meadows and steep mountain slopes. The area located in the dry temperate region comprising typical vegetation which disappears completely on the eastern slopes, dominated by a variety of economical species which play an important role in the rural life. The inhabitants are dependent on plant resources for food, fuel, timber, shelter, fodder/forage, household articles and traditional medicines in treating diseases like malaria, cancer, gastro-intestinal ailments, etc. This paper deals with the observations on traditional therapeutic application by the inhabitants of Paddar Valley. The ethno-botanical information on medicinal plants would not only be useful in conservation of traditional cultures and biodiversity but also community health care and drug development. Exploration survey in Paddar Valley has revealed that people collect and sell these medicinal species through local intermediaries / contractors to earn their livelihood. But the scientific cultivation and appropriate post-harvest management would improve employment opportunity and income of local farmers in the region.